The first All-Russian Congress of egyptologists - Olga Tomashevich; Evgeniya Anokhina (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi, 2023)
The paper is timed to the 200th anniversary of the decipherment of Egyptian hieroglyphs by J.-F. Champollion and is dedicated to a century-old event - the First All-Russian Congress of Egyptologists in Moscow. The 1920s were a real trial for the young Russian Egyptology: many scientists of both older and younger generations died or left the country; contacts with West European colleagues were broken; there was an acute shortage of specialized scientific literature; and all this developed on the background of a difficult economic situation in the country struggling for survival. The situation can be best described by the words attributed to the People’s Commissar for Education A.V. Lunacharsky: “Currently, the young Soviet Republic does not need Egyptologists”. Undoubtedly, the First All-Russian Congress of Egyptologists became an important moment for the formation of the scientific Egyptological community in the Soviet Russia. It was convened on August 17-20, 1922 on the initiative of the All-Russian Scientific Association of Oriental Studies and the Central Institute of Oriental Studies in Moscow. The meetings of the congress were held in the Museum of Fine Arts (now the Pushkin State Museum of Fine Arts) and the Moscow Archaeological Society. The events of the congress (list of participants and reports, resolutions) are reconstructed by the authors of the present paper on the basis of available sources. They show that despite all the difficulties, Egyptology in Russia at that time was actively developing branch and an interest in the culture of Ancient Egypt could be seen in the society. The authors also publish a previously unknown letter from the Petrograd Egyptologist Natalia Davydovna Flittner to the founder of the Berlin school of Egyptology Adolf Erman in which she describes the celebrations of the 100th anniversary of the decipherment of Egyptian hieroglyphs in Petrograd and Moscow, and also gives a general description of the development of Russian Egyptology of that time.